Simulation on personal computer of dynamic system having nonlinear damping force - Le, Nguyen Nhat (Vietnam Journal of Mechanics, 1993)
A dynamic system having nonlinear damping force and connected with a spring-damper element is simulated on personal computer. It is considered the influences of different parameters on the dynamic response of this system.